PERUBAHAN DAN PERBAIKAN KURIKULUM SUATU KEHARUSAN UNTUK MENINGKATKAN MUTU LULUSAN - Sri Winarni (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Curriculum is a reference to implement learning programme in achieving organization’sgoals. While goal of an organization is affected by current situation, and therefore, curriculummust be contextualize with the need of the latest situation. If the curriculum no longer cananswer the need of the organization, there is a demand of change. However, changes arenot always bring good impact; it is also have negative effects. Changes can be divided inthree phases: initiation phase, legitimating phase, and congruence phase. While the levelof changes can be small and limited (partial) or wide and basis (holistic). Working step onthe curriculum changes process include: identify the needs of changes on curriculum,mobilizing a curriculum changes, study on problems and need of community, study oncharacteristics and need of students, formulating educational goal, establishing learningactivity and subject matter, organize learning experience and planning of subject unit, testthe new curriculum, implementation of the new curriculum, evaluation and revision. Mainthing to be emphasized in the curriculum changes is the basic reason of curriculum changes,policy on education, educational programme, and other variable that affect the education.To avoid negative effect of the curriculum changes, therefore a systematically process ofcurriculum changes must be considered.Keywords: changes and curriculum changes.